Social-psychological determinants of hormonal contraceptive use intentions among adolescent girls in the Bono East Region of Ghana - Boamah-Kaali, Ellen Abrafi; Ruiter, Robert A. C.; Owusu-Agyei, Seth; Asante, Kwaku Poku; Mevissen, Fraukje E. F. (Frontiers in Public Health, 2023)
Introduction: The correct and consistent use of hormonal contraceptive (HC) methods by sexually active adolescent women can prevent pregnancy and avert the health and social consequences of unwanted pregnancy for both the mother and her child. Despite these benefits, research shows that HC use is rather low among adolescent women globally and especially among those in low and middle-income countries. This study was carried out to assess the social-psychological determinants of HC use intentions among adolescent women. Methods: A cross-sectional survey was conducted among 1203 young women from 70 communities within the Kintampo North Municipality and Kintampo South District in the Bono- East Region of Ghana from April 2021 to September 2021. Multiple linear regression analysis was used to identify factors associated with the intention to use HC among the entire sample of 1203 adolescent women and among two sub-samples of adolescent women based on HC use experience. Results: Attitude towards personal HC use ( = 0.268; p < 0.001), self-efficacy towards access and use of HC ( = 0.341; p < 0.001), and HC use experience ( = 0.647; p < 0.001) were found to be significant and unique correlates of HC use intention among the entire sample of adolescent women. Attitude toward personal HC use and self-efficacy toward access and use of HC were also associated with HC use intention in the two sub-samples significantly (p’s < 0.001). In addition, among participants with no HC experience, being a Christian as opposed to participants that affiliate themselves with Islam, Traditional religion, or being non-religious positively predicts future HC use (= 0.230; p < 0.01). Conclusion: In conclusion, our results demonstrate that different groups of adolescent women need different interventions, focusing on different determinants for the motivation to use HC. Comprehensive sexuality education, informing all adolescent women about the personal benefits of HC use and enhancing their skills in accessing and using HCs, can support their HC use intentions to promote their reproductive health and general well-being.